SEED ENHANCEMENT MENGGUNAKAN MATRICONDITIONING PLUS PADA BENIH PADI GOGO (Oryza sativa L.) YANG MENGALAMI DETERIORASI - Gusviani, Nisa Azzahra; Anwar, Aswaldi; Rozen, Nalwida (Agros Journal of Agriculture Science, 2024)
Upland rice is a type of rice that contributes to national rice production, but production is still categorized as low. Several problems in cultivating upland rice, such as the use of seeds produced from previous plantings and cultivation of upland rice plants which are still carried out once a year or once in one planting season, cause the seeds to undergo storage. Stored seeds have the potential to experience deterioration, which can reduce the quality of the seeds so that ultimately the plants do not grow optimally and have the potential to reduce production. This research used a completely randomized factorial design (CRD) which consisted of two factors, namely the comparison of the composition of matriconditioning plus and the length of immersion in matriconditioning plus. The combination treatment of the ratio of seed composition: rice husks ash: Trichoderma harzianum suspension (9:6:8) and soaking for 18 hours gives the best result because it can increase the maximum growth potential of the seeds to 98%, reduce the percentage of attack by pathogenic fungi to 11,67%, and have a higher test index value than other combinations. Key-words: Upland rice, seed deterioration, matriconditioning plusINTISARIPadi gogo merupakan salah satu jenis padi yang menyumbang produksi padi nasional, namun produksi masih dikategorikan rendah. Beberapa permasalahan dalam budidaya padi gogo seperti penggunaan benih yang diproduksi dari pertanaman sebelumnya dan budidaya tanaman padi gogo masih dilakukan sekali dalam setahun atau satu kali musim tanam menyebabkan benih telah mengalami penyimpanan. Benih yang disimpan berpotensi mengalami deteriorasi, sehingga dapat menurunkan mutu benih hingga akhirnya tanaman tidak tumbuh optimal dan berpotensi menurunkan produksi. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) Faktorial yang terdiri dari dua faktor, yaitu perbandingan komposisi dan lama perendaman benih dalam matriconditioning plus. Kombinasi perlakuan perbandingan benih: abu sekam padi: suspensi Trichoderma harzianum (9:6:8) dan perendaman benih selama 18 jam memberikan hasil terbaik karena dapat meningkatkan potensi tumbuh maksimum benih menjadi 98%, menurunkan persentase serangan jamur patogen menjadi 11,67% dan memiliki nilai uji indeks yang lebih tinggi dibandingkan kombinasi lainnya. Kata kunci: Padi gogo, deteriorasi benih, matriconditioning plus